2013
DOI: 10.1021/es304408y
|View full text |Cite
|
Sign up to set email alerts
|

Choices in Recreational Water Quality Monitoring: New Opportunities and Health Risk Trade-Offs

Abstract: With the recent release of new recreational water quality monitoring criteria, there are more options for regulatory agencies seeking to protect beachgoers from waterborne pathogens. Included are methods that can reduce analytical time, providing timelier estimates of water quality, but the application of these methods has not been examined at most beaches for expectation of health risk and management decisions. In this analysis, we explore health and monitoring outcomes expected at Lake Michigan beaches using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
(96 reference statements)
1
10
0
Order By: Relevance
“…A recent multi-site study in which 367 river samples were analyzed by E. coli culture (immediately) and enterococci qPCR (after freezing and storage) found comparable frequencies of BAV exceedance between the Day0 results of generated by the two methods [13]. At some of the same beaches that we studied (but several years earlier), qPCR BAV exceedance was less common than the E. coli culture BAV exceedance, consistent with our findings [30]. By contrast, in three beaches on an inland lake in Ohio, USA, the E. coli BAV was exceeded 24% of 59 samples, while the enterococci qPCR BAV was exceeded in 100% of 49 samples [29].…”
Section: Discussionsupporting
confidence: 88%
“…A recent multi-site study in which 367 river samples were analyzed by E. coli culture (immediately) and enterococci qPCR (after freezing and storage) found comparable frequencies of BAV exceedance between the Day0 results of generated by the two methods [13]. At some of the same beaches that we studied (but several years earlier), qPCR BAV exceedance was less common than the E. coli culture BAV exceedance, consistent with our findings [30]. By contrast, in three beaches on an inland lake in Ohio, USA, the E. coli BAV was exceeded 24% of 59 samples, while the enterococci qPCR BAV was exceeded in 100% of 49 samples [29].…”
Section: Discussionsupporting
confidence: 88%
“…A recent study also reported less frequent beach posting based on qPCR BAV than based on culture BAV, and the authors attributed such discrepancy to the fact that the published BAVs were derived from epidemiology studies at point source impacted beaches and may not perform well at sites with diffusive sources of Enterococcus (Nevers et al . ). Site‐specific conditions related to fate and transport of the source, prevalence of PCR‐inhibitory compounds (Noble et al .…”
Section: Discussionmentioning
confidence: 97%
“…Using these BAVs (70 colony-forming unit by EPA 1600 or 1000 calibrator cell equivalent by ddCt Taqman qPCR per 100 ml of water), we found that overall agreement on management decisions between culture and qPCR improved to over 92%, but qPCR results were much less likely to indicate a beach posting than EPA 1600 (Table 7). A recent study also reported less frequent beach posting based on qPCR BAV than based on culture BAV, and the authors attributed such discrepancy to the fact that the published BAVs were derived from epidemiology studies at point source impacted beaches and may not perform well at sites with diffusive sources of Enterococcus (Nevers et al 2013). Site-specific conditions related to fate and transport of the source, prevalence of PCR-inhibitory compounds (Noble et al 2010) and robustness of the chosen qPCR method against inhibition (Cao et al 2012) can also affect the culture-vs-qPCR difference.…”
Section: Discussionmentioning
confidence: 99%
“…3); the three ENT qPCR exceedances matched with ENT MF exceedances. While some studies have found similar RWQC exceedance results (Nevers et al, 2013), other researchers have found that ENT qPCR yielded more exceedances compared with ENT MF (Ferretti et al, 2013;Raith et al, 2014). There are significant advantages with the qPCR method, especially (i) reducing the time lag between sample collection and implementing management options and (ii) the confidence that qPCR results are equally effective predictors of gastrointestinal illnesses (Wade et al, 2008).…”
Section: Discussionmentioning
confidence: 99%